INPUT OF NUTRIENT (NITROGEN AND PHOSPHORUS) FROM THE CATCHMENT AREA INTO RAWAPENING LAKE OF CENTRAL JAVA - Agatha Sih Piranti; Diana RUS Rahayu; Gentur Waluyo (UNEJ e-Proceeding, 2016)
Nutrients (Nitrogen and Phosphorus) enter the waters in dissolved form or in sediment particles that reflect to condition of landuse activities that occur in the catchment area. This condition will determine the quality of the water and the lake productivity or trophic status. The purposes of this study were to assess how much nutrients input (N and P) that goes to Rawapening Lake and assess the biological response induced by lake. The observations was done by 4 times (2 times in the rainy season and 2 times in the dry season) in 9 of the river into the lake (River of Rengas, Panjang, Torong, Galeh, Parat, Legi, Muncul, Sraten, Kedungringin, Tuntang) as well as in 12 loc ations in the lake waters: area of Brebesan, Tourism of “Bukit Cinta”, Spring area, net cage 1, net cage 2, Kedungringin River estuary, and the outlet. The results showed that the TN input was up to 154,62 mg/sec and TP was up to 10,32 mg/sec. The Rawapening Lake had a deficit of TP up to 64.9% and TN up to 67.25%. It could be concluded that Rawapening lake had an acting as a sink and further it could served as a source of nutrients that lead to eutrophication condition.